Variations of refractive index and gain with carrier density in semiconductor injection lasers - Poh, B. S.; Poh, L. K. (Institution of Engineers, Malaysia, 1983)
A linear dependence of refractive index and gain coefficient on carrier density has been widely used by many authors in the investigation of the dynamic behaviour of semiconductor injection lasers. In this paper, the results of various authors on the variations of gain coefficient and refractive index with carrier density are assessed. It is found that the refractive index varies linearly with carrier density while the gain coefficient varies in a logarithmic manner with carrier density. The ratio, J..L, of the change in the real part of the effective refractive index to the change in the imaginary part is, therefore, proportional to N. It is suggested that such a J..L dependence on carrier density together with a logarithmic gain relationship should be used in the investigation of the dynamic behaviour of lasers